Vertical distribution and migration of microplastics in soils from Fars Province, Southwest Iran - Shekoufeh Forouzan; Sajjad Abbasi; Ali Akbar Moosavi; Majid Baghernejad; Sayyed Mahmoud Enjavinezhad; Andrew Turner (PLoS ONE, 2026)
Microplastics (MPs) in soils are becoming increasingly recognised as important terrestrial contaminants, yet their vertical distribution below the plough layer remains poorly understood. Here, we examined 76 genetic soil horizons from 27 profiles along four transects spanning managed and unmanaged land uses in Fars Province, southwest Iran, to depths of up to 140 cm. A total of 392 MPs were recovered from 71 of 76 samples, comprising 342 fibres (87.2%), 48 fragments or films and two spherules, with concentrations reaching about 320 particles kg -1 of dry soil. Raman analysis of 98 representative particles showed a dominance of polyamides, polyesters and polyolefins. MP abundance, size and polymer type were heterogeneous among sites and horizons, and only a few statistically significant relationships with soil properties were observed (notably inverse relationships with sand at Darab and silt at Sarvestan). MPs occurred throughout the profiles, including the deepest horizons, with no consistent size- or polymer-related fractionation with depth. These observations indicate sustained MP accumulation in soils and suggest that downward transport can occur under arid to semi-humid conditions through percolation, drying-cracking of the substrate and bioturbation. Because strong local point sources were not evident at most sites and fibres dominated the assemblage, atmospheric deposition is considered a major contributor at the soil surface, although additional source-specific data are needed to confirm this inference. The persistence and vertical mobility of MPs in Fars soils indicate potential risks to subterranean ecosystems and groundwater quality.